PENGARUH DISIPLIN KERJA, KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BPR BANK PURWOREJO - Azis, Diky; Achsa, Adhantu; Ikhwan, Khairul (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2022)
Human resources play an important role in an organization or company because human resources are the driving force for a company and the good of a company can be judged from the quality of existing human resources in a company. This study aims to determine how work discipline, competence and work motivation affect employee performance. The research method used in this study is a quantitative method. This study uses a descriptive analysis method with a quantitative approach, the analytical tool used in this study uses the IBM SPSS version 2.5.0. The data used are secondary data and primary data. The sample in this study were all employees of Perumda BPR Bank Purworejo who accessed 55 employees. Methodology of data analysis using multiple linear regression analysis. The results of the study can be seen that the work discipline variable has no significant effect on employee performance, the competency variable has a significant effect on employee work productivity, and the work motivation variable has a significant effect on employee work productivity.